Comparison of the Antibacterial Activities of Terminalia ferdinandiana Exell. Growing in Geographically Distinct Regions of Australia - Kim, Jinwoo; Rusford, Enoch John; Tiwana, Gagan; Alcorn, Sean Robert; Cock, Ian Edwin; Cheesman, Matthew James (Pharmacognosy Communications)
Background: Terminalia ferdinandiana Exell. fruit have been used by the First Australians as a nutritious food and as a medicine for thousands of years. The antibacterial properties of T. ferdinandiana fruit extracts are well reported. However, the therapeutic potential of plants growing in different locations and environmental conditions have not previously been compared. Aim: This study compares the antibacterial efficacy of fruit harvested from two distinct locations in Australia and correlates these activities with their physiochemical properties. Materials and Methods: The growth inhibitory activity of the T. ferdinandiana fruit extracts were evaluated using solid phase disc diffusion and liquid microdilution MIC assays. Artemia nauplii bioassays were used to screen and compare the extracts from both locations. Results: The T. ferdinandiana extracts prepared from fruits sourced from the two distinct regions of Australia inhibited the growth of the panel of bacteria screened, including a highly antibiotic MRSA strain. In general, the methanolic extracts were substantially better inhibitors of bacterial growth than the aqueous extracts, and extracts prepared using the Northern Territory (NT)-derived fruit were substantially more potent than the Western Australian (WA) fruit extracts. MICs substantially <1000 μg/mL were noted for the NT methanolic fruit extract against the reference S. aureus and MRSA bacterial strains respectively. The potency of this extract against the MRSA strain indicates that this extract may function via a distinct mechanism compared to the standard antibiotics tested. Interestingly, the greater antibacterial potency of the NT fruit extracts correlated to high ascorbic acid levels, indicating that the antibacterial mechanism may involve modulation of the redox state. All extracts were nontoxic in the Artemia nauplii toxicity assay, indicating their safety for therapeutic usage. Conclusion: The T. ferdinandiana fruit extracts prepared from both NT and WA each had noteworthy antibacterial activity, although greater activity was noted for the NT fruit extracts. This activity correlated with the antioxidant/ascorbic acid content of the extracts. All extracts were also nontoxic in the Artemia nauplii bioassay, although future studies using mammalian cell lines are required to confirm their safety for therapeutic use.
Keywords: Kakadu plum; Combretaceae; Antibiotic-resistance; MRSA; Redox modulation; Ascorbic acid.